A combination of the PI3K pathway inhibitor plus cell cycle pathway inhibitor to combat endocrine resistance in hormone receptor-positive breast cancer: a genomic algorithm-based treatment approach - Gul, Anita (Am J Cancer Res, 2018)
Cyclin-dependent kinase 4 (CDK4) and CDK6 together with D-type cyclins (D1, D2 and D3) to promote cell cycle entry and progression through G1 by inactivating retinoblastoma protein (RB) by inhibiting an INK4 family of CDK inhibitors (CDKN2A/B). Selective cyclin-dependent kinase inhibitors are game changers in the clinical management of hormone receptor-positive/HER2-negative advanced breast cancers. There are currently three CDK4/6 inhibitors that have been approved by the US Food and Drug administration: palbociclib, ribociclib, and abemaciclib. Although, the bulk of the data supporting the use of selective CDK4/6 inhibitors is currently in breast cancer patients with other tumor types are expected to benefit as well from this class of agents, which can counter proliferative signaling pathways and arrest cell cycle in early G1 phase. Areas of active interest include identifying predictive biomarkers for CDK4/6 inhibitors, deciding whether to continue CDK4/6 inhibitor after disease progression, creating novel treatment combinations and expanding the use of CDK4/6 inhibitors beyond hormone receptor-positive/HER2-negative advanced breast cancer. Right now, CCND1 amplification and CDKN2A/B loss have not sorted out biomarkers useful for the purpose. One of the most important clinical questions is how to use a CDK4/6 inhibitor with other targeted therapies. Here we provide a rationale that oncologists can use to sequence the CDK4/6 inhibitors along with the PI3K-AKT-mTOR pathway-specific inhibitor(s); future data will better guide this approach. In this review we have tried to (a) describe the specific cellular signals initiated following alterations in the cell cycle pathway genes and the PI3K pathway genes, (b) interrogate how these alterations/co-alterations influence the action of PI3K and cell cycle pathway-targeted drugs in different clinical trials and (c) understand the role of co-alterations towards the development of cell cycle inhibitors induced drug-resistance in ER+ breast cancers.